Pemberdayaan Kader Karang Taruna Desa melalui Implementasi Aplikasi AL CPR FOR CFR dalam Memberikan Pertolongan Pertama di Daerah Wisata - Alamsyah Alamsyah; Tut Handayani; Medy Wisnu Prihatmono; Amratul Jinan; Muh. Rival (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This community service program was designed to strengthen community preparedness in providing first aid for cardiac arrest cases in tourist areas, with a focus on empowering members of the Karang Taruna youth organization in Topejawa Village through the implementation of the AL CPR For CFR application. Cardiac arrest, known as a silent killer, is a serious health threat, especially when it occurs outside healthcare facilities, including tourist destinations that often lack immediate medical access. Therefore, equipping local youth with knowledge and skills in Basic Life Support (BLS) is an urgent necessity. The program involved 40 Karang Taruna members and was carried out in collaboration with the Public Safety Centre (PSC) of Takalar District. Training activities included lectures, group discussions, application-based learning, and simulation practice using standard mannequins. Pre-intervention assessments revealed that most participants had very low levels of understanding of BLS, with 86.11% categorized as poor. After the training, there was a significant improvement, with 94.44% of participants achieving a good level of knowledge. In addition, all participants were able to demonstrate cardiopulmonary resuscitation (CPR) skills according to standard operating procedures. The integration of theory, digital learning, and hands-on practice proved to be an effective combination for enhancing participants’ competencies. This program not only improved the capacity of local youth but also created a sustainable model of community empowerment. The empowerment of Karang Taruna as community first responders ensures that tourist villages have a resilient health safety network in facing cardiac arrest incidents. The program demonstrates that mobile-based applications can serve as practical, measurable, and adaptable tools for health education in various resource-limited contexts. Moving forward, it is recommended to expand the scope to other community groups, integrate continuous training with local health services, and conduct long-term monitoring to maintain participants’ skills and readiness.